2021
DOI: 10.3390/su13020626
|View full text |Cite
|
Sign up to set email alerts
|

How to Shape the Employees’ Organization Sustainable Green Knowledge Sharing: Cross-Level Effect of Green Organizational Identity Effect on Green Management Behavior and Performance of Members

Abstract: In a period of rapid information development and response to the impact of environmentalism on the company, how to effectively promote organizational members embracing knowledge sharing behavior through knowledge management will be an important issue in corporate green management. This article proposes a new integrated multi-level research framework based on organizational identity theory and psychological ownership theory to further analyze enterprise green management. Utilizing the data of 73 supervisors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 107 publications
2
25
0
Order By: Relevance
“…For example, green organizational identity [49] of TMTs may be one of the key antecedents of EPSs, because green organizational identity has been confirmed that it can influence corporates' green knowledge sharing, which may influence corporates' EPSs selection opportunities. Future studies should explore a broader range of antecedents for EPSs to provide an incremental contribution.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…For example, green organizational identity [49] of TMTs may be one of the key antecedents of EPSs, because green organizational identity has been confirmed that it can influence corporates' green knowledge sharing, which may influence corporates' EPSs selection opportunities. Future studies should explore a broader range of antecedents for EPSs to provide an incremental contribution.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…The process of human resources needs to be aligned with sustainability and the natural environment to achieve their goals. Green initiatives are to be incorporated in all human resources activities such as hiring, training, and compensation to create a sustainable culture within organizations [ 20 ]. The development of a green culture and incorporating it into the inner culture of an organization helps in building specific values in that organization [ 21 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…As leaders are also decision makers in hiring and choose to hire employees whose values align with their own or with company values, if leaders embracing green innovation are highly receptive to embracing green initiatives, then they will seek employees who also possess green values. People are one of the most important resources in a company and the creativity of employees is an important factor in organisational performance ( Chang and Hung, 2021 ). Additionally, employees are directed by leaders who let them give full play to their creativity to meet the aims directed by leaders.…”
Section: Hypoyhesis Developmentmentioning
confidence: 99%